2019
DOI: 10.1108/aaaj-04-2018-3467
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Napoleonic imperialism in Tuscany and the Kingdom of Naples

Abstract: Purpose The purpose of this paper is to examine the role of accounting in the enactment of the Napoleonic imperial project in Tuscany and the Kingdom of Naples in the early nineteenth century. Design/methodology/approach The study adopts the Foucauldian theoretical framework of governmentality and a comparative approach to highlight similarities and differences between the two regions. Findings The presence of different cultural understandings and structures of power meant that in Tuscany accounting mirror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Extant studies identify how accounting 'can be purposefully organised as a malleable object in order to reflect and enable different political ideologies as part of their hegemonic processes' (Li and Soobaroyen, 2021: 4). Consistently, and with very few exceptions (Bigoni et al, 2018;Di Cimbrini et al, 2019;Maran et al, 2016), research has assumed that an almost linear relationship exists between ideology and accounting, whereby accounting practices are mainly seen as a reflection of overarching ideologies, with their conception and functioning evolving with the transformation of the dominant ideology (Ezzamel et al, 2007;Goddard, 2002;Lehman and Tinker, 1987;Richardson, 1989;Xu et al, 2014Xu et al, , 2018Xu et al, , 2019Yee, 2009Yee, , 2012. In Fascist Italy the use of accounting in different organisations changed even if the underlying ideology did not.…”
Section: Discussionmentioning
confidence: 99%
“…Extant studies identify how accounting 'can be purposefully organised as a malleable object in order to reflect and enable different political ideologies as part of their hegemonic processes' (Li and Soobaroyen, 2021: 4). Consistently, and with very few exceptions (Bigoni et al, 2018;Di Cimbrini et al, 2019;Maran et al, 2016), research has assumed that an almost linear relationship exists between ideology and accounting, whereby accounting practices are mainly seen as a reflection of overarching ideologies, with their conception and functioning evolving with the transformation of the dominant ideology (Ezzamel et al, 2007;Goddard, 2002;Lehman and Tinker, 1987;Richardson, 1989;Xu et al, 2014Xu et al, , 2018Xu et al, , 2019Yee, 2009Yee, , 2012. In Fascist Italy the use of accounting in different organisations changed even if the underlying ideology did not.…”
Section: Discussionmentioning
confidence: 99%
“…Interdisciplinary accounting academics have explored the relationship between accounting and power (Hoskin and Macve, 1994; Napier, 2006), mapping the many overt and covert ways accounting can be recruited to support hegemonic forms of governance (Di Cimbrini et al. , 2020; Maran et al.…”
Section: Accounting Neoliberalism and Digitalisationmentioning
confidence: 99%
“…Accounting, neoliberalism and digitalisation Interdisciplinary accounting academics have explored the relationship between accounting and power (Hoskin and Macve, 1994;Napier, 2006), mapping the many overt and covert ways accounting can be recruited to support hegemonic forms of governance (Di Cimbrini et al, 2020;Maran et al, 2016). While accounting is also thought to have counter-hegemonic potential, its political potency tends to be obscured when it is portrayed as a neutral calculative practice capable of documenting financial and economic reality (Craig and Amernic, 2004;Josiah et al, 2010).…”
mentioning
confidence: 99%
“…These properties have enabled those in power to exercise 'control at a distance' as accounting reports can travel and be accumulated in 'centres of calculation' to be processed, compared and stored (Robson, 1992(Robson, , 1994. Studies have therefore identified how these properties were activated to ensure that rulers and governments can reach objectives as diverse as maximising tax receipts and tackling fraud (Sargiacomo, 2008), enacting far-reaching municipal reforms (Maran et al, 2014), and centralising power by silently removing the prerogatives of local elites (Di Cimbrini et al, 2020;Maran et al, 2016). Government intervention by means of accounting has extended to the management of territories in the achievement of specific goals.…”
Section: Literature Reviewmentioning
confidence: 99%